Wickerhamomyces anomalus relieves weaning diarrhea via improving gut microbiota and redox homeostasis using a piglet model. Issue 21 (12th October 2022) - Zhang, Yucheng; Liu, Hu; Yue, Zitian; Tan, Peng; Sun, Meige; Ji, Linbao; Bai, Yueyu; Ma, Xi
Abstract : W. anomalus acts as a probiotic to improve the growth performance and health of weaned piglets, which may shed light on the potential development of gut microflora in weaned animals. Abstract : Weaning stress commonly damages the intestinal barrier of mammals, resulting in gut microbiota dysbiosis, intestinal illness, and even severe diarrhea. Probiotics are used as a nutritional strategy to promote the health of humans and animals and the gut microbiota balance. Here Wickerhamomyces anomalus was applied as a probiotic supplement to a weaned piglet model to investigate its impacts on growth performance, antioxidant capacity, inflammation response, and intestinal health. Supplemental 1 g kg −1 10 8 cfu g −1 W. anomalus 13611 significantly decreased the feed conversion ratio (FCR), alleviated diarrhea, improved the apparent total tract digestibility of neutral detergent fiber (NDF) and gross energy (GE), increased the concentration of total antioxidant capacity (T-AOC) and catalase (CAT) in serum, and decreased the concentration of malondialdehyde (MDA) and pro-inflammatory cytokines such as interleukin-1β (IL-1β) in serum. Importantly, supplementation of W. anomalus 13611 also improved the gut microbiota, decreasing the relative abundance of Oxalobacteraceae, enriching the relative abundances of Lactobacillaceae and Lactobacillus, and increasing the relative abundances of two species of Lactobacillus ( helveticus and delbrueckii ). In conclusion, W. anomalus 13611 could effectively promote growth performance and alleviate diarrhea in a model of weaned piglets, which may be related to improved antioxidant activity, anti-inflammatory response, and alteration in the structure of the gut microbiota.